Revisiting thinking curriculum / Bawani Selvaraj - Bawani, Selvaraj (Universiti Teknologi MARA, Kedah, 2011)
Thinking is a process which occurs in context. Thinking discussed here is not confined to critical thinking but a combination of learning strategies and skills, creative thinking, metacognition and social skills. It is crucial to note that this is not a new subject fighting for a place in an already overcrowded curriculum but a distinct pedagogy strategy which is an important aspect to the approach of learning as well as teaching in all areas. The existing structure of a curriculum may remain but what needs to be done is to radically change the nature of the structure. It can be concluded that the understanding of thinking is crucial than the knowing of thinking